Taxonomic notes on the genus Euaspis Gerstäcker (Hymenoptera: Apoidea: Megachilidae) from Vietnam - Ngat, Tran Thi; Long, Khuat Dang; Phuong Lien, Nguyen Thi (Academia Journal of Biology, 2017)
Taxonomic notes on species of the genus Euaspis Gerstäcker, 1858 (Hymenoptera: Megachilidae) from Vietnam are presented. Three species of the genus are reported: E. aequicarinata Pasteels is recorded in the central highlands Vietnam (Kon Tum Province) beside the previous record of this species in the northwest (Hoa Binh Province); E. polynesia Vachal is widely recorded throughout Vietnam; the taxonomy of Vietnamese Euaspis basalis (Ritsema, 1874) is a misidentification, and it is indeed Euaspis diversicarinata Pasteels, 1980 and is a new record from Vietnam. A key to the females of Vietnamese species of Euaspis Gerstäcker and a redescription of the female of E. diversicarinata are given with illustrations.